Efektivitas Model Kooperatif Tipe Make A Match Berbantuan Flash Card Terhadap Peningkatan Kemampuan Perkalian Dan Pembagian Siswa Kelas IV - Muhamad Afrizal; Ela Suryani (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study is to describe the effectiveness of a cooperative model make a match type how to flash card the improved multiplication and division in 4th grade. The type of research is quasi experiment. The sample of research is A4th grade much as 33 students as experiment class and B4th much as 31 students as control class SDN Petukangan Utara 07 pagi Jakarta 2020/2021 period. Data gathering techniques is observation, test, and documentation. Studies showed that the use of make a match model how to flash card can be effective againts the increase in multiplication and division in 4th grade. This is verified according to: 1) there is a difference quality use make a match model how to flash card with expository model much as 2,30 and the significance is 0,000 < 0,05; 2) There is influence of make a match model how to flash card toward improvement multiplication and division in 4th grade with thitung = 14,974 > ttabel = 0,344 and the significance is 0,000 < 0,05; 3) there is increased ability multiplication and division in 4th grade with make with use make a match model how to flash card much as 4,31 and the significance is 0,000 < 0,05.